Penerapan Metode Fuzzy Tsukamoto Dalam Penentuan Harga Laptop Bekas - Marpaung, July Yanti; Ginting, Guidio Leonarde; Silalahi, Natalia (Forum Kerjasama Pendidikan Tinggi, 2020)
The wisdom in taking a decision on a particular problem is not an easy thing, because too much consideration is taken which is expected to help give a reason certain decisions must be taken. Likewise, the handling of the problem determines the price of used laptop units on the CV. Sumber Jaya Computer Medan. The type of used laptop that is determined by the price will be easier if it is done with an application, because it has done an assessment, then the things needed are like the quality of a used laptop according to the price, processor, hard disk, memory, VGA, Old Usage. Decision support system for determining a leptop price is very appropriate to be applied for handling problems that require self-resolution of computers for processing data specifications that follow selection with efficient and accurate calculations. By using Tsukamoto Fuzzy Logic reasoning in the processing of input and output data, as well as supporting information how much ranking is very supportive in making decisions to determine the price of a used laptop.